2017
DOI: 10.1016/j.ihj.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of rescue and primary percutaneous coronary interventions for acute ST elevation myocardial infarction

Abstract: In-hospital major adverse cardiac events (MACE) are similar in both rescue and primary intervention groups, supporting the former as a practical option for patients with no immediate access to PCI facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In order to minimize such delays in coronary reperfusion a pharmaco-invasive strategy is suggested. A prompt pharmaco-invasive technique compared favourably with primary PCI in terms of reducing morbidity and death in STEMI patients, according to numerous research from close by nations 21,22,23 .…”
Section: Stemi Care -Structurementioning
confidence: 99%
“…In order to minimize such delays in coronary reperfusion a pharmaco-invasive strategy is suggested. A prompt pharmaco-invasive technique compared favourably with primary PCI in terms of reducing morbidity and death in STEMI patients, according to numerous research from close by nations 21,22,23 .…”
Section: Stemi Care -Structurementioning
confidence: 99%
“…On the other hand, Rahuman et al [25], from the cardiology PCI Clinic of the National Hospital of Sri Lanka (NHSL), included all acute SEMI patients from March 2013 to April 2015 who were presenting with <24 h door-to-balloon time for primary PCI and <72 h door-to-balloon time, 90 min after failed thrombolysis for rescue PCI, and their in-hospital results were analyzed, comparing rescue and primary PCI patients. They concluded that major adverse cardiac events in hospital are similar in both primary and rescue intervention groups, supporting the rescue as an option for patients with no immediate access to PCI facilities.…”
Section: Regardingmentioning
confidence: 99%